Rancang Bangun Alat Bantu Penyusun Cetak Biru Jaringan Induk Komunikasi Dan Informasi Berbasis Peta Digital Studi Kasus Kabupaten Lombok Utara - Ni Wayan Eka Widiyani; Ida Bagus Ketut Widiartha; Sri Endang Anjarwani (Journal of Computer Science and Informatics Engineering (J-Cosine), 2018)
The Technology of Master Plan is a something for planning over the next few years in a region. North Lombok Regency is a newly established district and requires the master plan to accelerate the development process especially in ITC section. Development of master plan in this region is difficult to do because the location of Government offices is spread, with a very wide area and hilly contours. To create a master plan in a region like this tool that is based on a digital map that allows viewing maps, routes, contours and distances between points on the map.The purpose of this research is to build a system that can give information about Government service locations, route, distance and elevation to determine the network infrastructure in every government service locations. This system is developed by CodeIgniter Framework and using PHP and HTML programming language, it is also using Google Maps API to display route, distance, and elevation. In this research using 5 steps as system development, that are defining system requirements, system planning, coding and implementation, testing and documentations. The user can determine the type of network in every government service locations that based on the result of the route, distance and elevation by using Google Maps API. This system is using black box and MOS for testing. The result of black box testing the function in the system has been running nicely and the result of MOS got 53,54% answers are agreed for this system.